Evaluation of the Association between Genetic Polymorphism of Interleukin-1 Beta (–511C/T and +3953C/T) and Cervical Cancer Susceptibility - Pratap, Pushpendra D.; Raza, Syed Tasleem; Zaidi, Ghazala; Kunwar, Shipra; Eba, Ale; Rajput, Muneshwar (South Asian Journal of Cancer, 2024)
Cervical cancer (CC) is the leading cause of cancer-related mortality among women, primarily caused by persistent human papillomavirus (HPV) infection, especially in developing countries. A proinflammatory cytokine, emerging as a major facilitator of carcinogenesis, is termed interleukin-1 beta (IL-1β), which characterizes host-environment interactions. Numerous epidemiological studies have revealed that IL-1β gene polymorphisms have been associated with numerous malignancies, but in the context of CC, results of these studies were inconclusive. Thus, our study aimed to explore the relationship between IL-1β polymorphisms (-511C/T and +3953C/T) and CC susceptibility. Genotyping was conducted on 192 CC patients and 200 healthy controls through polymerase chain reaction-restricted fragment length polymorphism. HPV analysis was done through real-time polymerase chain reaction, and the serum concentration of IL-1β was measured by enzyme-linked immunosorbent assay. Women with CT and TT genotypes of IL-1β -511C/T had a threefold increased risk of CC (odds ratio [OR], 3.60; 95% confidence interval [CI], 2.132-6.063; p < 0.001 vs. OR, 3.34; 95% CI, 1.952-5.713; p < 0.001) compared to controls. Women with the T allele of IL-1β -511C/T polymorphism were associated with increased CC susceptibility (OR, 2.00; 95% CI, 1.51-2.66; p = 0.0001) compared to controls. No significant difference was found between patients and controls in the genotype or allele frequencies of IL-1β +3953C/T polymorphism (OR, 0.93; 95% CI, 0.56-1.55; p = 0.86 vs. OR, 0.95; 95% CI, 0.72-1.26; p = 0.74). There was no significant association found between IL-1β -511C/T promoter (OR, 2.41; 95% CI, 0.46-12.76; p = 0.28 vs. OR, 1.64; 95% CI, 0.13-21.10; p = 0.7) and +3953C/T (OR, 3.76; 95% CI, 0.44-31.82; p = 0.19 vs. OR, 0.21; 95% CI, 0.01-3.92; p = 0.25) polymorphisms in tobacco chewers and smokers compared to controls. The level of serum concentration of IL-1β was significantly higher in cases compared to controls. Our results conclude that IL-1β -511C/T polymorphism is associated with CC susceptibility.
Keywords: ELISA; gene polymorphism; HPV; PCR-RFLP; RT-PCR